What would be the derivative the square roots? For instance if I have actually \$2 sqrtx\$ or \$sqrtx\$.

You are watching: Derivative of the square root of x

I"m unsure just how to uncover the derivative the these and include them specifically in something prefer implicit.  Let \$f(x) = sqrtx\$, then \$\$f"(x) = lim_h o 0 dfracsqrtx+h - sqrtxh = lim_h o 0 dfracsqrtx+h - sqrtxh imes dfracsqrtx+h + sqrtxsqrtx+h + sqrtx = lim_x o 0 dfracx+h-xh (sqrtx+h + sqrtx)\ = lim_h o 0 dfrachh (sqrtx+h + sqrtx) = lim_h o 0 dfrac1(sqrtx+h + sqrtx) = dfrac12sqrtx\$\$In general, you have the right to use the reality that if \$f(x) = x^t\$, climate \$f"(x) = tx^t-1\$.

Taking \$t=1/2\$, gives us the \$f"(x) = dfrac12 x^-1/2\$, i m sorry is the same as we obtained above.

Also, recall the \$dfracd (c f(x))dx = c dfracdf(x)dx\$. Hence, you can pull out the consistent and then identify it.

re-publishing
mention
follow
answer Jun 29 "12 in ~ 21:52
user17762user17762
\$endgroup\$
1
13
\$egingroup\$ This is the finest answer here, since it doesn't assume that the power rule (which is basic to prove when the exponent is a positive integer) automatically uses when the exponent is not a positive integer. \$endgroup\$
–user22805
Jun 29 "12 at 22:47
include a comment |
29
\$egingroup\$
\$sqrt x=x^1/2\$, therefore you simply use the power rule: the derivative is \$frac12x^-1/2\$.

share
mention
follow
reply Jun 29 "12 in ~ 21:50 Brian M. ScottBrian M. Scott
\$endgroup\$
11
13
\$egingroup\$
Another opportunity to uncover the derivative the \$f(x)=sqrt x\$ is to use geometry. Imagine a square through side length \$sqrt x\$. Climate the area the the square is \$x\$. Now, let"s extend the square top top both sides by a tiny amount, \$dsqrt x\$. The brand-new area included to the square is:\$\$dx=dsqrt x * sqrt x + dsqrt x * sqrt x + dsqrt x^2.\$\$ This is the amount of the sub-areas added on each side the the square (the orange locations in the photo above). The critical term in the equation over is very small and deserve to be neglected. Thus:

\$\$dx=2*dsqrt x * sqrt x\$\$

\$\$fracdxdsqrt x=2 * sqrt x\$\$

\$\$fracdsqrt xdx=frac12*sqrt x\$\$

(To go from the 2nd step come the last, flip the fountain on both sides of the equation.)

Reference: significance of Calculus, thing 3

re-publishing
mention
monitor
reply Dec 22 "17 in ~ 19:45 Armin MeisterhirnArmin Meisterhirn
\$endgroup\$
3
include a comment |
8
\$egingroup\$
The Power preeminence says the \$fracinvernessgangshow.netrmdinvernessgangshow.netrmdxx^alpha=alpha x^alpha-1\$. Using this come \$sqrtx=x^frac12\$ gives\$\$eginalignfracinvernessgangshow.netrmdinvernessgangshow.netrmdxsqrtx&=fracinvernessgangshow.netrmdinvernessgangshow.netrmdxx^frac12\&=frac12x^-frac12\&=frac12sqrtx ag1endalign\$\$However, if you room uncomfortable applying the Power preeminence to a fractional power, consider applying implicit differentiation to\$\$eginaligny&=sqrtx\y^2&=x\2yfracinvernessgangshow.netrmdyinvernessgangshow.netrmdx&=1\fracinvernessgangshow.netrmdyinvernessgangshow.netrmdx&=frac12y\&=frac12sqrtx ag2endalign\$\$

share
point out
monitor
answer Jun 29 "12 in ~ 22:04 robjohn♦robjohn
\$endgroup\$
4
\$egingroup\$
Let \$f(x) = sqrtx = x^1/2\$.

\$\$f"(x) = frac12 x ^-1/2\$\$

\$\$f"(x) = frac12x^1/2 = frac12sqrtx\$\$

If you write-up the details implicit differentiation problem, it may help. The basic guideline of writing the square root together a fractional power and then making use of the power and also chain rule accordingly should be fine however. Also, remember that you can simply pull the end a constant when taking care of derivatives - view below.

See more: My Girlfriend Wants To Peg Me ? Should I Let My Girlfriend Peg Me

If \$g(x) = 2sqrtx = 2x^1/2\$. Then,

\$\$g"(x) = 2cdotfrac12x^-1/2\$\$

\$\$g"(x) = frac1x^1/2 = frac1sqrtx\$\$

re-superstructure
point out
monitor
edited Jun 29 "12 in ~ 22:08
answer Jun 29 "12 in ~ 21:52
JoeJoe
\$endgroup\$
1
\$egingroup\$
Use the product dominance \$(fg)"=f"g+fg"\$ and also take \$f=sqrtx=g\$. Then\$\$x"=1=(sqrtx cdot sqrtx)"=(sqrtx)"sqrtx+sqrtx(sqrtx)"=2sqrtx(sqrtx)".\$\$It complies with that \$\$(sqrtx)"=frac12sqrtx\$\$

re-superstructure
mention
monitor
reply Nov 10 in ~ 9:22
Nicky HeksterNicky Hekster
\$endgroup\$
-2
\$egingroup\$
\$sqrtx\$Let \$f(u)=u^1/2\$ and \$u=x\$That"s \$fracdfdu=frac12u^-1/2\$ and also \$fracdudx=1\$But, by the chain preeminence \$fracdydx=fracdfdu•fracdudx=frac12u^-1/2 •1=fracddxsqrtx\$Finally\$frac12sqrtx\$

re-superstructure
cite
follow
edited Oct 22 "17 at 12:20
Daniel Fischer
answered Oct 22 "17 in ~ 10:59
user488395user488395
1
\$endgroup\$
2
Highly active question. Knife 10 reputation (not counting the association bonus) in order to answer this question. The reputation necessity helps defend this question from spam and non-answer activity.

## Not the answer you're looking for? Browse various other questions tagged calculus derivatives or ask your very own question.

Upcoming events
Featured top top Meta
0
How to identify functions with square roots
-1
Derivative that \$sqrtx\$ using Symmetric Derivative Formula
1
A alternative geometric (visual) systems to the derivative the square-root
connected
0
finding the derivative that a square root duty
0
Derivative: Square root
1
Derivative that Square root Polynomial?
9
How have the right to I inspect if mine derivative because that an implicit function is correct?
1
derivative through square root
1
Derivative of Square root Visual
2
how to compute this derivative of a square root of a sum?
2
"Square root" that a derivative operator?
hot Network concerns more hot inquiries
question feed

invernessgangshow.net
firm
ridge Exchange Network
site design / logo design © 2021 stack Exchange Inc; user contributions licensed under cc by-sa. Rev2021.11.23.40809

invernessgangshow.netematics ridge Exchange works finest with JavaScript permitted 